2020
DOI: 10.1038/s41467-020-16525-w
|View full text |Cite
|
Sign up to set email alerts
|

The ABCG2 Q141K hyperuricemia and gout associated variant illuminates the physiology of human urate excretion

Abstract: The pathophysiological nature of the common ABCG2 gout and hyperuricemia associated variant Q141K (rs2231142) remains undefined. Here, we use a human interventional cohort study (ACTRN12615001302549) to understand the physiological role of ABCG2 and find that participants with the Q141K ABCG2 variant display elevated serum urate, unaltered FEUA, and significant evidence of reduced extra-renal urate excretion. We explore mechanisms by generating a mouse model of the orthologous Q140K Abcg2 variant and find male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 59 publications
5
96
0
Order By: Relevance
“…In the fructose loading study, baseline serum urate levels were also elevated in the high BMI group, with similar baseline FEUA values compared with the low/normal BMI group. Studies of urate transport indicate that the machinery of transporters is essentially at capacity at baseline and that increasing FEUA with increasing load represents “spilling”, with the amount of uric acid filtered saturating reabsorptive transporters, so that extra uric acid is excreted [ 5 ]. Collectively, these observations suggest that people with high BMI have a higher capacity for uric acid reabsorption at baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fructose loading study, baseline serum urate levels were also elevated in the high BMI group, with similar baseline FEUA values compared with the low/normal BMI group. Studies of urate transport indicate that the machinery of transporters is essentially at capacity at baseline and that increasing FEUA with increasing load represents “spilling”, with the amount of uric acid filtered saturating reabsorptive transporters, so that extra uric acid is excreted [ 5 ]. Collectively, these observations suggest that people with high BMI have a higher capacity for uric acid reabsorption at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This was an experimental intervention study designed to identify factors that influence serum urate and fractional excretion of uric acid (FEUA) responses to inosine. The primary aim of the study was to determine the influence of genetic variants on inosine-induced hyperuricaemia in healthy adult volunteers, and these results have been reported in full [ 5 ]. The study protocol also pre-specified analysis of the effects of BMI on serum urate and FEUA responses to inosine.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…With the mechanistic understanding of the CFTR trafficking, there now exist the therapeutic options for cystic fibrosis patients (e.g., lumacaftor-ivacaftor, tezacaftor-ivacaftor) (65,66). Correction strategies using trafficking modifiers or chemical chaperones are being explored in preclinical and clinical settings for other transporters [e.g., ABCB11 encoding Bile Salt Export Pump (BSEP) and progressive familial intrahepatic cholestasis type 2 (67-69); ABCG2 encoding BCRP and gout (70,71)]. To date, a number of studies reported alterations in the level and cellular localization of certain OATs and OATPs under disease conditions such as cancer and liver diseases (72,73).…”
Section: Overview Of the General Cellular Processing Of Transportersmentioning
confidence: 99%
“…Immunosuppressive drugs are required for increasing the life span of the cell while using pluripotent cells. Rapid proliferation and yield of a higher number of useful cells are the advantages of pluripotent stem cells (Hoque et al, 2020). The intestinal stem cells are present at the base of crypts, where they are sustained in a speci ic microenvironment which help to conserve the multipotency to allow the generation of all epithelial cell lineages from the differentiation of progenitor cells (Jebaraj et al, 2015).…”
Section: Stem Cell Therapymentioning
confidence: 99%